Welders' pneumoconiosis: tissue elemental microanalysis by energy dispersive x ray analysis. Issue 1 (January 1988) - Funahashi, A; Schlueter, D P; Pintar, K; Bemis, E L; Siegesmund, K A
Abstract : Histological examination on lung tissue obtained from 10 symptomatic welders was performed by two certified pathologists without the knowledge of the patients' clinical condition. In all cases, there was some degree of interstitial fibrosis; in five the degree of fibrosis was considered to be moderate to pronounced. The tissue was also analysed by energy dispersive x ray analysis and elemental contents were compared with age matched controls. There was a large amount of iron in the lungs of welders but the silicon content did not differ from the control subjects. No specific foreign element was detected. It is concluded that (1) interstitial pulmonary fibrosis is seen in some welders and (2) the cause of fibrosis does not appear to be coexisting silicosis.